2014
DOI: 10.1002/jms.3308
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry imaging: a new vision in differentiatingSchistosoma mansonistrains

Abstract: Schistosomiasis is a neglected disease with large geographic distribution worldwide. Among the several different species of this parasite, S. mansoni is the most common and relevant one; its pathogenesis is also known to vary according to the worms' strain. High parasitical virulence is directly related to granulomatous reactions in the host's liver, and might be influenced by one or more molecules involved in a specific metabolic pathway. Therefore, better understanding the metabolic profile of these organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
0
28
0
2
Order By: Relevance
“…For example, the granuloma formation occurs by the reaction of host immune response mediated by parasite glycoconjugates; therefore, the greater abundance of glucosylceramides (GlcCer) in one strain compared to another, the higher pathogenicity [32,34]. The same study using high-resolution mass spectrometry (HRMS) showed that phosphatidic acid (PA), phosphatidylserine (PS), phosphatidylethanolamine (PE), triacylglycerol (TG), and diacylglycerol (DG) are involved in the differentiation of S. mansoni strains [34]. In respect to maturation, immature and mature eggs present also been differentiated using Matrix-Assisted Laser Desorption/ Ionization-Time of Flight Mass Spectrometry (MALDI-TOF-MS).…”
Section: Mature and Immature Eggsmentioning
confidence: 99%
“…For example, the granuloma formation occurs by the reaction of host immune response mediated by parasite glycoconjugates; therefore, the greater abundance of glucosylceramides (GlcCer) in one strain compared to another, the higher pathogenicity [32,34]. The same study using high-resolution mass spectrometry (HRMS) showed that phosphatidic acid (PA), phosphatidylserine (PS), phosphatidylethanolamine (PE), triacylglycerol (TG), and diacylglycerol (DG) are involved in the differentiation of S. mansoni strains [34]. In respect to maturation, immature and mature eggs present also been differentiated using Matrix-Assisted Laser Desorption/ Ionization-Time of Flight Mass Spectrometry (MALDI-TOF-MS).…”
Section: Mature and Immature Eggsmentioning
confidence: 99%
“…Despite the ongoing belief that schistosomes cannot utilize fatty acid (or β‐) oxidation to support OXPHOS (Barrett, ; Ferreira et al ., 2014a,b), the schistosome genome nevertheless encodes the enzymes of the β‐oxidation pathway, through which fatty acids are catabolized into the TCA cycle (Berriman et al ., ), and mitochondrial oxygen consumption in schistosomes can be inhibited by etomoxir, a drug that blocks the transfer of activated fatty acids into mitochondria for subsequent oxidation (Huang et al ., ). Moreover, genetic loss of function of Acyl CoA synthase and Acyl CoA dehydrogenase, key enzymes in the β‐oxidation pathway, also results in diminished mitochondrial oxygen consumption.…”
Section: Fatty Acid Oxidation Is Required For Egg Productionmentioning
confidence: 99%
“…With respect to investigation of the molecular content of the tissue within its morphological context, it was the technique of mass spectrometry imaging (MSI) that made it possible [24]. In parasitology, one study examined the chemical markers of the surface of S. mansoni by MSI to distinguish between the sexes and the strains [25], while another study dealt with the same organism and investigated the composition of internal organs by histological sections [26]. Because of the technical limits of MSI, in both cases, the focus was on the relatively small molecules of triacylglycerols and phosphatidylcholines, not on proteins.…”
Section: Introductionmentioning
confidence: 99%